The Effect of Satisfaction and Motivation on Purchase Interest (Case Study: Madrasah Ibtidaiyah Tahfidz Al-Qur'an Al Furqon Ponorogo) - Anant Adji; Muhammad Kurnia Rahman Abadi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2022)
Satisfaction and motivation are thought to have an influence on consumer purchase interest, this is based on the concept that in order to attract customers, the approach to customers must be carried out properly in order to create a comfortable atmosphere for customers to shop. This study aims to determine the effect of satisfaction and motivation on the buying interest of students' guardians to send their children to Islamic Education Institutions at Madrasah Ibtidaiyah Tahfidz Al-Qur'an Al-Furqon Ponorogo. The efforts of data collection in this research by distributing questionnaires to a sample of 97 respondents from a total population of 147. The analysis used was validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, and hypothesis testing. The results showed that: satisfaction and motivation have a positive and significant effect on consumer purchase interest. Satisfaction (X1) has a positive and significant effect on consumer purchase interest. Meanwhile, motivation (X2) is also significant, has a positive effect on consumer purchase interest in Madrasah Ibtidaiyah MI Tahfidz Qur'an Al-Furqon Ponorogo education services.